The relationship between perceived control and panic buying during the COVID-19 pandemic - Olivia, Olivia; Jatnika, Ratna; Sodjakusumah, Tutty (Goodwood Publishing, 2023)
Purpose: This study aimed to examine the negative correlation between perceived control and panic buying during the COVID-19 pandemic. Research Methodology: It was conducted on middle-aged women using WhatsApp were married and were domiciled in Java. The criteria used was convenience sampling with a total of 193 respondents. Perceived control was measured with a questionnaire adapted from Berkenstadt Perceived Personal Control, while panic buying was measured by Lins and Aquino Panic buying Scale. Additionally, a test was conducted to evaluate the correlation coefficient between the two variables. Result: The results showed that middle-aged women using WhatsApp had moderate perceived control and panic buying, indicating no significant negative correlation between the two. Limitation: Uneven demographic proportions and a one-year retrospective period in this study may impact data accuracy due to reliance on respondent recall. Contribution: Providing a new perspective on factors associated with panic buying.